The effect of diverting activity on fatigue during isokinetic exercise using large muscle groups - Rotstein, A.; Jablonowsky, R.; Bar-Sela, S.; Malamud, G.; Inbar, O.; Tenenbaum, G. (The Journal of Strength and Conditioning Research, 1999)
Previous investigations have demonstrated the fatigue-reducing effect of diverting activity during intervals of repeated isotonic exertion of small muscle groups. The purpose of the present investigation was to evaluate the effect of diverting activity on performance of large muscle groups (legs) working isokinetically. Fifteen trained males (mean ± SD: 17.4 ± 0.51 years old, 74.6 ± 9 kg in weight, 184 ± 6.6 cm in height) participated in this study. Each subject performed three leg extension exercise sessions. Each exercise session included two bouts of all-out leg extension repetition for 40 seconds at a constant angular velocity of 180°·s 1 on an Ariel computerized isokinetic machine with a 1-minute rest period in between. During the 1-minute interval between each bout, one of the following treatments was applied: (a) passive rest, (b) active recovery consisting of low intensity leg work, and (c) diverting activity during which the subject was instructed to squeeze a 2× 2 cm rubber sponge between his thumb and his middle finger to the beat of a metronome. The order of treatment was randomly assigned. The main finding of the present investigation indicates that diverting activity as used in this study reduced muscle fatigue, similarly to active recovery and more effectively than passive rest. Average force decreased by 30.1 N after diverting activity compared to a decrease of 39.8 N after passive recovery. The findings indicate that diverting activity may reduce fatigue developed with isokinetic exercise performed with large muscle groups.